Systemic Regulators of Skeletal Muscle Regeneration in Obesity - Sinha, Indranil; Sakthivel, Dharaniya; Varon, David E. (Frontiers in Endocrinology, 2017)
Skeletal muscle maintenance is a dynamic process and undergoes constant repair and regeneration. However, skeletal muscle regenerative capacity declines in obesity. In this review, we focus on obesity-associated changes in inflammation, metabolism, and impaired insulin signaling, which are pathologically dysregulated and ultimately result in a loss of muscle mass and function. In addition, we examine the relationships between skeletal muscle, liver, and visceral adipose tissue in an obese state.